EFFECT OF HYPOCHLOROUS ACID ON SURFACE ROUGHNESS AND WETTABILITY OF ZINC OXIDE EUOGENOL IMPRESSION PASTE - J.Taha, Israa; M. Abass, Shorouq ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Aim: Dental impression materials may be infected when touched with patient plaque, saliva, and blood and immediately contaminated with potentially harmful germs. The spread of infection can be prevented through disinfection of the impression materials. The disinfection solution may change the impression materials’ properties, The study goal was to investigate the effects of two disinfectants(2% glutaraldehydes (G.A.) and hypochlorous acid(HOCl) 200ppm,400ppm for ten minutes) on the wettability and surface roughness of the zinc oxide-eugenol (ZOE) impression material. Materials and Methods: Eighty zinc oxide- eugenol impression material specimens were randomly classified into four groups for each test ten specimens ,A custom-produced mold, a circular in shape 2mm thickness and 20 mm in diameter made. A profilometer device was used for the surface roughness (Ra) measurement, and a goniometer device was used for the contact angles measurement to determine Wettability, The Statistical analysis was done using IBM’s Statistical Package for the Social Sciences.The One Way Analysis of Variance (ANOVA) test was used to data analysis. Results: The results of this study revealed that HOCl and 2%glutaraldehyde demonstrate no effect on the wettability and surface roughness of zinc oxide-eugenol impression paste compared to the control group (P>0.05). Conclusion: Considering the limitation of this investigation, the hypochlorous acid (200ppm 400ppm) is recommended for use as an efficient disinfection without a negative impact on the surface roughness and wettability of the ZOE impression paste